Simulation-Based Training of Ultrasound-Guided Procedures in Radiology – A Systematic Review - Kahr Rasmussen, Niklas; Andersen, Tobias Thostrup; Carlsen, Jonathan; Østergaard, Mia Louise; Konge, Lars; Albrecht-Beste, Elisabeth; Nielsen, Michael Bachmann (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To perform a systematic review of the effect of simulation-based training (SBT) of percutaneous abdominal and thoracic ultrasound-guided procedures and to assess the transfer of procedural competence to a clinical context.Materials and Methods This systematic review was conducted in accordance with the PRISMA statement. Pubmed, Embase, Web of Science, and the Cochrane Library were searched for studies assessing procedural competence after SBT. Two authors independently reviewed all studies and extracted data. Risk of bias was assessed using the Cochrane tool for randomized studies (RoB) and non-randomized studies (ROBINS-I). Quality of evidence was assessed using the GRADE approach.Results 42 studies were included. 6 were randomized controlled, 3 non-randomized controlled, and 33 non-randomized non-controlled. 26 studies examined US-guided abdominal procedures, 13 examined thoracic procedures, and 3 examined both. The results favored SBT compared to other educational interventions and found that training was superior to no training. Only two studies examined the transfer of procedural skills to a clinical context. All studies had a high or critical risk of bias. Thus, the quality of evidence for the effect of SBT on procedural competence was low, and evidence for its transfer to a clinical context was very low.Conclusion The evidence supporting SBT of percutaneous abdominal and thoracic US-guided procedures remains insufficient due to methodological problems and a high risk of bias. Future studies should be randomized and single-blinded, use assessment tools supported by validity evidence, compare different educational strategies, and examine the transfer of skills to a clinical setting.
Keywords: ultrasonography; simulation training; clinical competence; educational measurement; image-guided biopsy